2017
DOI: 10.1097/cad.0000000000000445
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival with somatostatin analog and chemotherapy and prognostic factors for treatment in 165 advanced neuroendocrine tumor patients with Ki-67 20% or less

Abstract: The objectives of this study were to compare progression-free survival (PFS) with somatostatin analog (SSA) versus chemotherapy (CTx) in first-line therapy and to determine the patient group in which these treatments were more effective in neuroendocrine tumors (NETs) with a Ki-67 index of 20% or less. Patients who received SSA or CTx and had unresectable locally advanced and metastatic NETs with a Ki-67 index of 20% or less were retrospectively selected from 13 centers in the Turkish database between 2000 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Other studies that evaluated the median PFS in patients on LAN treatment for the management of GEP or bronchial NETs are summarised in Supplementary File 1 (Table 1a, b) [4,5,[11][12][13][14][15][16][17][18][19][20][21]. The PFS reported in our study is in agreement with other publications [4,5,13,14,16,20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Other studies that evaluated the median PFS in patients on LAN treatment for the management of GEP or bronchial NETs are summarised in Supplementary File 1 (Table 1a, b) [4,5,[11][12][13][14][15][16][17][18][19][20][21]. The PFS reported in our study is in agreement with other publications [4,5,13,14,16,20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Like the findings observed with PRRT, poorer performance status [ 172 ], symptomatic tumors [ 173 ] and the prior lack of primary tumor resection [ 172 ] are associated with decreased PFS with SSA treatment ( Table 2 , Right Panel). Two different studies report significant decreases in PFS in patients with baseline (pre-SSA) documentation of disease progression [ 173 , 174 ], suggesting a significant but mild anti-tumor activity of SSAs in patients with panNENs, as well as with GI-NENs.…”
Section: Predictive Factors For Response To Ssa In Advanced Pannensmentioning
confidence: 74%
“…Several studies report a worse clinical outcome in patients with elevated baseline levels of CgA [ 172 , 175 ], whereas the decrease in CgA levels after SSA treatment is predictive of an improved PFS [ 176 , 177 ]. A recent post hoc analysis of the Phase 3 CLARINET study demonstrated that 5-HIAA responders had significantly improved PFS with lanreotide treatment ( p = 0.007), while no significant difference in PFS was observed between CgA responders and no-responders.…”
Section: Predictive Factors For Response To Ssa In Advanced Pannensmentioning
confidence: 99%
See 1 more Smart Citation
“…Martyn et al [ 17 ] reported that compared with the placebo group, the SSA group could significantly prolong progression-free survival (PFS) in patients with metastatic enteropancreatic neuroendocrine tumors (Ki-67 < 10%). Ersin et al [ 18 ] found that PFS in the SSA group was 21 months, which was better than the chemotherapy group as their first-line treatment for NET (Ki-67 ≤ 20%). PRRT has become an effective treatment for the NETs which express sufficient SSR.…”
Section: Discussionmentioning
confidence: 99%